Factors influencing university selection among students in Sekolah Menengah Kebangsaan Seri Serdang / Atiqah Diyana Abd Wahid - Abd Wahid, Atiqah Diyana (Faculty of Business Management, 2017)
The government of Malaysia has given emphasis on the education field since the Independence Day until today. They believe that education is the key to develop Malaysia to become a better nation and to help Malaysia become a fully develop nation by 2020 (Norasmah Othman, Noorasiah Sulaiman, Poo Bee Tin, Harinder Kaur T. Singh, 2012). According to L. Battagan and c. Boja (2011), for a society to have long term health prosperity, educated workers as well as leaders for future, education structure would be the best to help achieve that. Universities and other higher education institutes has experienced increasing competition to attract both local and international students in Malaysia (T. Mazzarol,1998). However, in the last decade of the 20th century, globalization is the reason for the changes in the education industry in Malaysia (Ministry of Education,2008).